2006 International Conference on Wireless and Mobile Communications (ICWMC'06) 2006
DOI: 10.1109/icwmc.2006.61
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating 802.11 Mac Anomaly Using SNR To Control Backoff Contention Window

Abstract: The standard 802.11 presents a MAC anomaly when the same Access Point operates stations with different data rates. Analysis shows that the degradation is higher for the station with a high data rate that operates with good signal to noise ratio (SNR). Consequently, the station with low SNR has higher throughput then stations with high SNR. To evaluate the anomaly an experimental test was created to obtain the WLAN behavior with wireless host transmitting with low SNR together with hosts with high SNR. The anom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
5
0
3
Order By: Relevance
“…A substantive research on mitigating the effect of MAC layer performance anomaly in multi-rate WLANs has been presented in literature. The work proposed in [2][11] [13] [15] are of premier importance to this research study. In [13] authors have proposed an algorithm for performance anomaly reduction using open flow access points.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…A substantive research on mitigating the effect of MAC layer performance anomaly in multi-rate WLANs has been presented in literature. The work proposed in [2][11] [13] [15] are of premier importance to this research study. In [13] authors have proposed an algorithm for performance anomaly reduction using open flow access points.…”
Section: Related Workmentioning
confidence: 99%
“…This assertion ensures that the effect of MAC layer performance anomaly can be substantially reduced by using time-varying and time-correlated channels with Rayleigh fading effects. The work presented in [2] mitigates the effect of MAC anomaly by controlling the value of backoff contention window based on signal strength of a node. Authors have concluded that, lower values of contention window for nodes having higher SNR considerably reduces the effect of MAC anomaly.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Our objects of study are the works regarding workbench setups to measure, control and mitigate this anomaly. Branquinho et al (2006) successfully identified and mitigated the MAC anomaly using Signal to Noise Rate (SNR) measures in a controlled workbench environment. Guirardello (2008) demonstrated the possible use of QoS, Quality of Service (Oliveira et al, 2015), to mitigate a MAC Anomaly.…”
Section: Introductionmentioning
confidence: 99%
“…Hence when the Medium Access Control (MAC) layer of the IEEE802.11e standard priories a STA with a low transmission rate (because of the type of its content), it can jeopardize the access of other STAs with better transmission capacities and better SNRs, but with contents of lower priority. Consequently, a second anomaly is created (Branquinho et al, 2006), which can be understood as a priorization of the first anomaly of IEEE802.11 networks. In this context, this study proposes a QoS policy based on the IEEE802.11e standard implementation, aiming to optimize the usage of wireless networks resources.…”
Section: Introductionmentioning
confidence: 99%